IMPLEMENTATION OF INNOVATIVE LEADERSHIP STYLE IN CORPORATE GOVERNANCE: PRINCIPLES OF LEADERSHIP 4.0 (World Bulletin of Management and Law, 2025)
This article analyzes the issues of implementing innovative leadership (Leadership 4.0) principles in corporate governance. It emphasizes the need to further improve traditional management approaches and develop innovative leadership competencies within corporate structures. The aim of the study is to explore the main directions of implementing Leadership 4.0 principles in corporate governance and to assess their impact on performance indicators. Using systematic analysis, comparative analysis, and survey methods, the study highlights the intellectual, socio-emotional, and digital competencies of innovative leadership. The obtained results serve as a scientific basis for improving corporate management, digitalizing corporate strategies, and enhancing decision-making processes in joint-stock companies
Keywords: corporate governance; Leadership 4.0; innovative leadership